A novel epoxy-terminated polyethylene modified asphalt with low-viscosity and high storage stability. (13th June 2022) - Li, Mengru; Luo, Chunjia; Zhu, Liuyu; Li, Huayi; Cong, Peiliang; Feng, Yangyang; Yan, Luke
Graphical abstract: Highlights: A novel low molecular weight epoxy-terminated-PE (EPE) was prepared for asphalt. EPE reduces mixing and compaction temperatures of asphalt. EPE modified asphalt shows excellent storage stability. Abstract: The storage stability of polyethylene (PE) modified asphalt is a major constraint to its wide application. In addition, PE raises the mixing and compaction temperature of asphalt, causing environmental pollution. The effective synthesis of stable and environmentally friendly PE modifiers is an important and challenging topic. We propose a strategy to reduce the molecular weight of PE while adding functionalized end group to PE. The obtained low molecular weight epoxy-terminated-polyethylene (EPE) for modified asphalt is storage stable, reduces mixing and compaction temperatures of asphalt, and reduces environmental pollution. The difference between the top and bottom softening points of asphalt containing 3 wt% and 5 wt% EPE was 1.25 °C and 0.7 °C, which exceeded most previously reported PE-modified asphalt. In addition, EPE, due to its low molecular weight, reduces the high temperature viscosity of asphalt, achieving lower mixing and compaction temperatures. Besides, dynamic shear rheometer (DSR) and multiple stress creep recovery (MSCR) data showed that the rheological properties of EPE modified asphalt were also significantly improved. This work will provide further guidance for the application of PE in asphalt.